2022
DOI: 10.1103/physrevlett.129.054501
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Equilibrium of Large Scales in Three-Dimensional Hydrodynamic Turbulence

Abstract: We investigate experimentally three-dimensional (3D) hydrodynamic turbulence at scales larger than the forcing scale. We manage to perform a scale separation between the forcing scale and the container size by injecting energy into the fluid using centimetric magnetic particles. We measure the statistics of the fluid velocity field at scales larger than the forcing scale (energy spectra, velocity distributions, and energy flux spectrum). In particular, we show that the large-scale dynamics are in statistical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These findings are also important from a practical perspective since they predict the mean value and statistics of the power injected by a large-scale force in turbulence. This could be experimentally investigated by adding a large-scale propeller in the experiment in which largescale equipartition was observed [24]. Moreover, since the proper variables of the system are identified, our work paves the way to use equilibrium statistical mechanics and maximum entropy techniques to model geophysical large scales, as already successfully done for the simpler 2D case [20].…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…These findings are also important from a practical perspective since they predict the mean value and statistics of the power injected by a large-scale force in turbulence. This could be experimentally investigated by adding a large-scale propeller in the experiment in which largescale equipartition was observed [24]. Moreover, since the proper variables of the system are identified, our work paves the way to use equilibrium statistical mechanics and maximum entropy techniques to model geophysical large scales, as already successfully done for the simpler 2D case [20].…”
mentioning
confidence: 77%
“…Recent numerical and experimental investigations report equipartition of energy at large scales [21][22][23][24], as predicted by the TEE, at least provided some constraints on the forcing mechanism are put [25,26]. TEE have also been found able to capture bifurcation between turbulent states [27][28][29].…”
mentioning
confidence: 89%
“…This article focuses on the statistics of velocity structure functions at separations larger than the forcing scale. Gorce & Falcon (2022) studied the second-and third-order structure functions and found that they are independent of separation r of two measured points, which we believe is a result of low resolution. This article shows that the probability density functions (p.d.f.s) of velocity difference at large separations are close to, but deviate from, the Gaussian distribution.…”
Section: Introductionmentioning
confidence: 88%
“…Numerical and experimental results have justified the large-scale statistical equilibrium in 3-D HIT (Cichowlas et al. 2005; Dallas, Fauve & Alexakis 2015; Cameron, Alexakis & Brachet 2017; Alexakis & Biferale 2018; Alexakis & Brachet 2019, 2020; Gorce & Falcon 2022; Hosking & Schekochihin 2023). The dynamics of scales larger than the forcing scale are of interest for many flows where the energy flux is zero, e.g.…”
Section: Introductionmentioning
confidence: 94%
“…The induced flows subsequently interact to form a central HIT region with small mean flow. Recent innovative techniques have also been developed to generate turbulence in laboratories via injection of vortex rings and magnetic particles (Gorce & Falcon 2022;Matsuzawa et al 2023). We note that some facilities use rotating elements (e.g.…”
Section: Synthetic Jets and Pointwise Energy Injectionmentioning
confidence: 99%